En offentlig hemmelighed: Når sikkerhedspolitik går fra statsmandskunst til allemandseje - Petersen, Karen Lund; Tjalve, Vibeke Schou (Politik, 2015)
New forms of information and communication technology, surveillance and data collection have blurred the boundary between public and private responsibility: whereas it used to be only the statesman and his selected few who made decisions regarding national security, it is, in the age of unpredictability and resilience, a very wide range of both state and civilian actors who, on a daily basis, participate in the national intelligence practice. is article argues that a new security politics, driven by the notion of unpredictable risks and made possible by new data and surveillance technologies, has created a new kind of intelligence practice in which ethico-democratic questions about ownership, responsibility and control are urgent. e intelligence services’ current answer to these questions is more ‘method’ and better ‘procedures’. is is, however, not good enough. By identifying not just an ethos of rules but also an ethos of judgement in the Western tradition of state, this article recommends that we rediscover and democratise the line of thinking in our bureaucratic ethos that emphasises the ability to make (self-)critical judgements.